The Utilization of Calcium in Watermelon Rind Extract for Osteoporosis Drug Agent - Asiyah, Siti Nur; Prayoga, Bagus Putra; Hartatiek, Hartatiek; Ahmad, Norhayati (JPSE (Journal of Physical Science and Engineering), 2023)
Calcium is one of the essential minerals for the body, especially in the elderly and pregnant women. Using natural materials containing calcium is very important, especially natural materials that are only used as waste, such as watermelon rind. Watermelon rind has a calcium of 31 mg. Therefore, it is very efficient to be used. The manufacture of this osteoporosis drug does not refer to calcium from watermelon rind extract alone. However, it is supported by other herbal ingredients such as rhizomes (ginger, curcuma, turmeric, and fingerroot). The method of extracting calcium from watermelon rind used the destruction method. After being extracted, the extraction and some mixed with the rhizomes were tested, such as calcium levels, XRF, XRD, and FTIR tests. The result of the study showed that all samples were confirmed to have calcium. High calcium content of 13.30 percent was found in the watermelon rind extract sample from watermelon fruit measuring 6 kg mixed with rhizomes. All samples' calcium level test results had a dominant value of 495 ppm.DOI: 10.17977/um024v8i12023p001